2019
DOI: 10.1371/journal.pone.0224364
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjusted kidney volume measured in the bench surgery on one-year renal function in kidney transplantation

Abstract: BackgroundKidney transplantation is the treatment of choice in patient with end stage chronic kidney disease, offering the best long term survival and greater Quality of Life in this group of patients. Graft volume was correlated with improved renal function in living donor transplantations. The primary aim of this study was to correlate renal volume adjusted to body surface area with renal function one year (estimated glomerular filtration rate; eGFR) after kidney transplantation.MethodsThis single-center, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…Likewise, previous studies found an association with donor’s kidney size at ultrasounds or kidney volume at the CT scan or at the time of surgery and recipient’s renal function [43‒47]. Our data do not support a close correlation between donor’s kidney size and recipient’s kidney function, possibly because of the use of a less sensitive technique [48].…”
Section: Discussioncontrasting
confidence: 94%
“…Likewise, previous studies found an association with donor’s kidney size at ultrasounds or kidney volume at the CT scan or at the time of surgery and recipient’s renal function [43‒47]. Our data do not support a close correlation between donor’s kidney size and recipient’s kidney function, possibly because of the use of a less sensitive technique [48].…”
Section: Discussioncontrasting
confidence: 94%
“…24 Higher overall kidney volume, assessed at the time of transplantation, predicted a higher eGFR at 1-y posttransplant. 30 Furthermore, patients with decreased overall graft size ascertained at 1 y, compared to 1 mo after transplantation were at significantly increased risk of subsequent graft dysfunction and end-stage graft failure. 31 Unfortunately, none of these studies correlated overall renal size with histopathologic markers of acute or chronic renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…The percentile curves may also have some clinical implications in renal transplantation. Although today, one usually does not take into account kidney size to decide which kidney should be given to which patient, in general, larger donor kidneys result in better graft function at follow up [32]. The percentile curves in our article will allow clinicians to estimate expected kidney size of potential donors before organ removal or imaging.…”
Section: Discussionmentioning
confidence: 99%